Steel City Gospel : Protestant Laity and Reform in Progressive-Era Pittsburgh. - Zahniser, Keith A. (Religion in history, society & culture, 2005)
This book tells the complex story of Pittsburgh citizens' struggle to define and eliminate the problems plaguing their city during the Progressive Era.